An Investigation Of Note Taking Strategies Used By Efl Learners - Keskes, Said . (University of Eloued جامعة الوادي, 2022)
The nature of teaching at University requires students to use higher level study skills than those they used at middle and high school. Note taking, particularly, is very important to learn from lectures in the field of higher education. First Year students of English at Setif 2 University are expected to use efficient note taking during lectures with little experience in this skill. The aim of this study is to explore whether students are using efficient note taking strategies during lectures. For that, three research methods were employed under the approach of mixed methods research. These are: questionnaire, observation, and document analysis. Findings reveal that students do not use efficient strategies to promote note taking. Therefore more extensive instruction on note taking should be administered.
Keywords: Note taking ; note taking strategies ; lectures